2008
DOI: 10.1111/j.1600-6143.2007.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes of Liver Retransplantation: An Analysis of Trends and the Impact of Hepatitis C Infection

Abstract: Retransplantation (RT) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 30 publications
(57 reference statements)
1
50
0
2
Order By: Relevance
“…86 UNOS data from 1994-2005 demonstrated that despite improved outcomes with RT overall, HCV patients continue to have worse patient and graft survival rates compared to non-HCV patients. 87 Additional variables such as increased severity of illness pre-RT may account for decreased survival in this group following RT. As a result, the role of RT in HCV+ LT recipients remains controversial due to concerns of accelerated recurrence leading to rapid graft loss.…”
Section: Retransplantation (Rt)mentioning
confidence: 99%
“…86 UNOS data from 1994-2005 demonstrated that despite improved outcomes with RT overall, HCV patients continue to have worse patient and graft survival rates compared to non-HCV patients. 87 Additional variables such as increased severity of illness pre-RT may account for decreased survival in this group following RT. As a result, the role of RT in HCV+ LT recipients remains controversial due to concerns of accelerated recurrence leading to rapid graft loss.…”
Section: Retransplantation (Rt)mentioning
confidence: 99%
“…Some studies have suggested HCV-infection as a risk factor of mortality [25][26][27][28]. Rosen et al [27] analyzed 1356 patients who underwent RT from the United Network for Organ Sharing (UNOS) from 1990 to 1996.…”
Section: Retransplantation In Hcv-infected Patients: General Considermentioning
confidence: 99%
“…Hepatitis C and donor age were associated with a poor prognosis on univariate analysis, but neither had enough power to be included in a predictive model. Similarly, Ghabril et al [28] have recently evaluated 1034 HCV-infected patients and 1249 non-HCV-infected patients who underwent RT between 1994 and 2005. Patient and graft survival were significantly lower for HCV-infected compared to non-HCV-infected patients who underwent RT at least 90 days after primary LT.…”
Section: Retransplantation In Hcv-infected Patients: General Considermentioning
confidence: 99%
“…Moreover, other recent studies do not identify HCV recurrence as a predictor of increased mortality in comparison with other etiologies with the exception of reLT performed during the first year after primary LT (Ghobrial et al, 2002). Based on multivariate analysis it was shown that early reLT performed in HCV-positive patients is an independent predictor of morality after reLT, indicating that severe hepatitis C recurrence (such as FCH or another reason for early graft dysfunction) should be a contraindication for retransplantation (Ghabril et al, 2008). Multiple prognostic scores were implemented to facilitate decisions which reLT would be unreasonable due to compromised graft and patient survival.…”
Section: Retransplantation In Hcv Recurrencementioning
confidence: 90%